Sustainability of biodegradable plastics: a review on social, economic, and environmental factors - Moshood, Taofeeq D.; Nawanir, Gusman; Fatimah, Mahmud (Taylor and Francis Ltd, 2021)
In line with the recent economic growth, especially in developing countries, human concern for the environment has increased over time. This paradigm shift has influenced many developing countries to pay more attention to the issues related to the use of synthetic plastics. Both industry and consumers are intrigued to discover the: economic characteristics, environmental consequences, and social attitudes to the benefits of biodegradable plastics. Biodegradable plastics are useful in packaging, agriculture, gastronomy, consumer electronics, and the automotive industry. This paper seeks to explain the prospects of biodegradable plastics regarding social, economic, and environmental sustainability and recognizes the latest advances in enzyme-based biodegradation of plastics in order to reduce plastics' negative effects and to make the environment safe. A multi-disciplinary strategy is a unique approach, with studies carried out across the triple bottom line (TBL) approach on three distinct sustainability concepts (economic characteristics, environmental consequences, and social attitudes). These three subjects were carefully chosen for their respective targets. This paper has used ATLAS.ti 9 software tools to thoroughly analyze the literature to save, identify, and assess this study's data. Therefore, the research showed that the environmental component was the most critical factor with the economic second and social third. We review bio-based and biodegradable polymers and highlight the value of biodegradable end-of-life management.